The Diagnosis of Exogenous Lipoid Pneumonia Caused by the Silent Aspiration of Vegetable Oil Using a Lipidomic Analysis - Shimizu, Tetsuo (Intern Med, 2019)
We herein report a case of refractory exogenous lipoid pneumonia that was successfully attributed to vegetable oil through a lipidomic analysis of bronchoalveolar lavage fluid (BALF). As a 25-year-old woman diagnosed with lipoid pneumonia experienced repeated exacerbations and improvement, we performed a BALF lipidomic analysis. The major lipid components were oleic acid, linoleic acid, and α-linolenic acid, which are constituents of vegetable oil. She stopped consuming any vegetable oil and has since experienced no instances of lipoid pneumonia relapse. A lipidomic analysis appears to be useful for identifying causative lipids, since patients with lipoid pneumonia are sometimes unaware of aspiration episodes.